Revitalisasi Cucupatian melalui Pengembangan Bahan Ajar Bahasa Indonesia di Sekolah Dasar - Fahimah*, Fahimah; Fitriani, Maudiya; Rianta, I Gusti Kadek Agus; Sartika, Yana; Hanafi, M.; Luthfiyanti, Lita (Alinea: Jurnal Bahasa, Sastra, dan Pengajaran, 2024)
This article describes the development of Indonesian language teaching materials based on cucupatian for grade IV elementary school students. This research uses an ethnopedagogical approach with in-depth interviews and direct observation. There are several results of this research. First, the Indonesian language teaching materials at SDN Teluk Tiram 2 currently do not include Banjar culture. Second, cucupatian can be included in the descriptive text material in chapter 6 "Satu Titik" with the teaching module "Cucupatian Descriptive Text" and physical teaching media "Cuba Pang". Third, teaching materials can increase insight into Banjar culture, Banjar and Indonesian vocabulary, and can trigger the implementation of a thematic approach in the Merdeka Curriculum. In addition, it can be an example of making a culture-based teaching module.Keywords: teaching materials; cucupatian; Indonesian Abstrak: Artikel ini memaparkan pengembangan bahan ajar bahasa Indonesia berdasar cucupatian untuk siswa SD kelas IV. Riset ini menggunakan pendekatan etnopedagogi dengan wawancara mendalam dan observasi langsung. Terdapat beberapa hasil riset ini. Pertama, bahan ajar bahasa Indonesia yang ada di SDN Teluk Tiram 2 saat ini belum memuat budaya Banjar. Kedua, cucupatian dapat dimuat dalam materi teks deskripsi pada bab 6 “Satu Titik” dengan  modul ajar “Teks Deskripsi Cucupatian” dan media ajar fisik “Cuba Pang”. Ketiga, bahan ajar dapat menambah wawasan budaya Banjar, kosakata bahasa Banjar dan bahasa Indonesia, serta dapat memicu penerapan pendekatan tematik dalam Kurikulum Merdeka. Selain itu, bisa menjadi contoh pembuatan modul ajar berbasis budaya.Katakunci: bahan ajar; cucupatian; bahasa Indonesia